Conventional ovarian stimulation vs. delayed single dose corifollitropin alfa ovarian stimulation in oocyte donors: a prospective randomized study. Tail trial - Alvarado Franco, Carlos Alberto; Bernabeu García, Andrea; Suñol Sala, Jordi; Guerrero Villena, Jaime; Albero Amorós, Sonia; Llacer, Joaquin; Delgado Navas, Ricardo Antonio; Ortiz, José A.; Pitas, Anna; Castillo Farfan, Juan Carlos; Bernabeu Pérez, Rafael (Frontiers in Reproductive Health, 2023)
The present study compares two protocols for ovarian controlled stimulation in terms of number of cumulus-oocyte complexes and metaphase II oocytes. We employed a single injection of 150mcg of corifollitropin alfa after a 7-day oral contraceptive pill-free interval for TAIL group and a conventional administration of corifollitropin alfa after a 5-day OCP-free interval with additional rFSH from 8th of ovarian controlled stimulation. Prospective, randomized, comparative, non-inferiority, opened and controlled trial carried out in 180 oocyte donors 31 were excluded, 81 were randomized to the control group and 68 to the TAIL group. No differences were found in the number of follicles larger than 14 and 17 mm at triggering day. However, a lower number of cumulus-oocyte complexes and metaphase II oocytes were obtained in TAIL group compared to the control group, expressed as median (interquartile range): 10.5 (5.5–19) vs. 14 [11–21] and 9 (4–13) vs. 12 (9–17) respectively. Additionally, the incidence of failed retrieval or metaphase II oocytes = 0 was higher in TAIL group 7(10.3%) vs. 1(1.2%) p = 0.024. The use of a single injection of corifollitropin alfa after a 7-day oral contraceptive pill-free interval in oocyte donors resulted in a lower number of cumulus-oocyte complexes and metaphase II oocytes. No additional rFSH was administered in this group. Clinical Trial Registration:https://www.clinicaltrialsregister.eu/ctr-search/trial/2019-001343-44/results.